Multilingualism and language choice in the imperial Roman army - Felice, E (2019)
This thesis is a sociolinguistic study of language choice in the Roman army, focused on the period between the first and the third centuries AD. Its main aims are to revisit our understanding of language choice in military administration, and to identify patterns of language choice in communication between soldiers and their associates. These themes are approached through a tripartite framework inspired by discourse analysis, which includes the concepts of audience, identity, and practicality. The case studies examined in the thesis show that Latin was not the only language of military administration, but played a vital role in written contexts where the army acted in its institutional function. This “institutional” use of Latin is reflected at the interpersonal level, where it enabled soldiers and their associates to express belonging to the military experience. Latin and other languages appear also as lingue franche and as markers of different types of identities, often connected with questions of prestige. Overall, this thesis enables us to refine our understanding of the reasons that prompted soldiers and their associates to use one language instead of another when a choice was available, and to renew our appreciation for cross-linguistic communication in Roman military environments.